Hybrid total arch replacement via ministernotomy for Stanford type A aortic dissection - Liu, Xing; Liu, Xinyi; Yu, Hong; Yang, Yuehang; Shi, Jiawei; Zheng, Qiang; Wang, Kan; Liu, Fayuan; Li, Ping; Deng, Cheng; Hu, Xingjian; Wu, Long; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Type A aortic dissection (TAAD) is a cardiovascular emergency condition with high mortality rate. Hybrid total aortic arch replacement using endovascular graft for the descending aorta repair results in favorable outcomes and has been recommended as an alternative procedure for the higher-risk category patients. Our institution started applying the upper ministernotomy incision technique for the hybrid procedures back in 2018. Methods We collected patients who underwent hybrid total arch replacement (HTAR) via ministernotomy (96) and total arch replacement with frozen elephant trunk (TAR + FET) procedures (99), between 2018 and 2021. The baseline information, intraoperative and postoperative characteristics have been compared. Kaplan-Meier analysis was used for survival evaluation. Cox regression were applied to identify the independent predictor of mortality. Results The baseline characteristics between the two patient groups were compared and found similar, except that RBC counts were higher (p = 0.038) and the ascending aorta diameter was smaller (P = 0.019) in the “HTAR” group relative to the “TAR + FET” group. The cardiopulmonary bypass time (P < 0.001), the aortic cross clamp time (P < 0.001), the operation duration (P = .029), ICU (P = 0.037) and postoperative hospital stay (P = 0.002) were shorter in the “HTAR” group. The “HTAR” group exhibited also significantly lower levels of intraoperative transfusion (all <0.001) characteristics than the “TAR + FET” group. The hospital mortality and 1-year mortality revealed similar patterns in both groups. Conclusion HTAR via ministernotomy have similar short term prognosis, and also reduced the ICU and postoperative hospital stay. In all, The application of the ministernotomy technique in HTAR was safe and technically feasible and may benefit individual patients as well as hospitals in general.